Health condition of hospitalized elderly with fêmur fracture - Pilotto Casagranda, Letícia; dos Santos, Fernanda; Lange, Celmira; Mirapalheta Pereira de Llano, Patrícia; Martin Milbrath, Viviane; Hoffmann Pinto, Andressa (O Mundo da Saúde, 2016)
The health status of the elderly is a determinant that can enable them to enjoy growing old with a preserved quality of life. The objective of this study was to gain an understanding into the health conditions of the elderly before they are hospitalized for femoral fractures. This was a descriptive, cross-sectional study conducted between February 2012 and February 2013, with 108 elderly patients admitted to a hospital in the southern region of the state of Rio Grande do Sul, and diagnosed with femoral fractures. The data were gathered through individual interviews, with a standardized, pretested questionnaire. Outcome assessment was carried out by descriptive statistics. The results showed a prevalence of females, an age range of 70-80-year-olds, white and school-educated individuals. Systemic hypertension was the chronic disease that most plagued these elderly individuals, followed by eye problems. When asked whether they were afraid of falling, 66% of the elderly responded affirmatively, and 68% already had a certain difficulty getting around. Falls were the main reason for femoral fractures among the elderly studied. It was also observed that they used several medications to stay healthy. Most of these multi-medication users were afraid of falling, had problems getting around and did not exercise or engage in physical activity. Understanding the health conditions of these elderly individuals enables healthcare professionals and managers to create strategies to prevent against diseases and aggravators, thereby promoting a healthy aging process, and ultimately directing investments at the prevention of falls, thus avoiding fractures.